Implementation of Animated Video Development as a Media for Strengthening Student Character in Primary Schools - Lestari, Wahyu Adinda Wardani; Dahnial, Irfan (Journal of Elementary School Education, 2024)
Article aimed at exploring the development of animated videos as a character strengthening tool in elementary schools. The method employed was a literature review using 10 journal articles published within the last 10 years. The study found that using animated videos as a medium for character strengthening in elementary school students is a suitable approach. The urgency of animated videos includes adaptation to the digital generation, enhancing interest and learning motivation, effectiveness in delivering moral messages, and simplifying complex concepts through video. Implementation of animated video development as a character strengthening medium in elementary schools should consider thorough planning, feasibility testing, and other pertinent factors.